2020
DOI: 10.1109/access.2020.2964726
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Survey and Empirical Study of Meta-Learning for Classifier Selection

Abstract: Classification is the key and most widely studied paradigm in machine learning community. The selection of appropriate classification algorithm for a particular problem is a challenging task, formally known as algorithm selection problem (ASP) in literature. It is increasingly becoming focus of research in machine learning community. Meta-learning has demonstrated substantial success in solving ASP, especially in the domain of classification. Considerable progress has been made in classification algorithm reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 78 publications
0
43
0
Order By: Relevance
“…In this study, we used Sentinel-2 multispectral and Sentinel-1 SAR imagery with large swath width to accommodate regional-scale studies. However, due to the spectral and spatial resolutions of satellite-based RS data are generally low, the phenomenon of "the same object with different spectrum" and "the different object with same spectrum" often occurs when observing grassland communities on a large scale [22,38], thus reducing the accuracy of classification.…”
Section: The Effect Of Input Variables On Classification Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we used Sentinel-2 multispectral and Sentinel-1 SAR imagery with large swath width to accommodate regional-scale studies. However, due to the spectral and spatial resolutions of satellite-based RS data are generally low, the phenomenon of "the same object with different spectrum" and "the different object with same spectrum" often occurs when observing grassland communities on a large scale [22,38], thus reducing the accuracy of classification.…”
Section: The Effect Of Input Variables On Classification Accuracymentioning
confidence: 99%
“…The other reason for the difficulty in distinguishing grassland communities using spaceborne mid-resolution RS images is that the performance of the classification models used to classify grassland communities is suboptimal [3]. In previous studies of vegetation classification, classification models (including classifiers and their hyperparameters) were usually determined empirically without selecting the optimal ones based on the specific study [22,23]. Notably, studies suggest that the selection of classification models has a significant impact on the classification results [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Classification has used for prediction purposes; traditional rule-based algorithm does not provide any prediction feature for the unknown dataset. Confusion matrix provides various measurement of accuracy in prediction, where rule-based algorithm cannot perform this [7]. CNN is a deep learning model where computation complexity is higher than machine learning models.…”
Section: Introductionmentioning
confidence: 99%
“…Existing evidence has shown that by combining prior knowledge and context, humans can gain experience on multiple prior tasks over bounded episodes, where the learned abstract experience is generalized to improve future learning performance on new concepts. Inspired by this, a computational paradigm called meta-learning [7,8] is proposed to simulate the ability of humans to learn generalized task experience, aiming to allow machines to acquire prior knowledge from similar tasks and quickly adapt to new tasks. The meta-learning process is more data-efficient than traditional machine learning models by extracting the crossdomain task goals in a dynamic selection [9,10].…”
Section: Introductionmentioning
confidence: 99%